Physical and Mental Health Status, Life Style and Quality of Life among Hijra /Transgender Woman: An Exploratory Study in Chandigarh, India - Dr. Sushma kumari Sani, Dr. Sandhya Ghai, Raju Ram Runwal, Mrs. Manjula Thakur,; Mittal, Mr. Sandeep (International Journal of Innovative Research in Medical Science, 2018)
Objective: Transgender people are a highly vulnerable group in India with high level of HIV and mental health burden. While HIV interventions among hijra/transgender women are being scaled up in various parts of India, limited information is available on their physical, mental health status and quality of life thus, a study was conducted to assess the health status, and quality of life of hijra/transgender people in India. Methodology: A purposive sampling technique 60 participants were enrolled who are registered non-government organization in Chandigarh. Data was collected by interview, physical assessment and health records analysis. We used Standardized tools as Back Depression Inventory, General Well Being Scale, Social Adjustment Scale, WHO QOL BREF, Bio Physiological assessment and life style Questioner for data collection. The data was analyzed by using descriptive and inferential statistics like frequency distribution, mean, and Pearson’s correlation coefficient. Results: The mean age was 33±10.6 years Standard deviation 10.6. More than one-fourth were illiterate and only 26.75% were educated up to matriculation. A majority (90%) of them were engaged taking badhai and getting money. Majority (92%) of the participants had central obesity (WHR > 0.85cm). Only few reported diabetes mellitus (6.7%), hypertension (6.7%) and HIV infection (6.7%). Half of the participants had mild depression and 40% had borderline to severe depression. Forty two percent had stress. Quality of life revealed that 11.6 % had poor Quality of life and about forty six percent of participants had average Quality of life. Conclusion: Poor quality of life, less education, occupation, multiple sexual partner, obesity and substance abuse are some health issues are needed to be stressed to improve the overall quality of life of transgender people.